Crucial role of high-mobility group box 2 in mouse ovarian follicular development through estrogen receptor beta - Yamaguma, Yu; Sugita, Naohiro; Choijookhuu, Narantsog; Yano, Koichi; Lee, Deokcheol; Ikenoue, Makoto; Fidya; Shirouzu, Shinichiro; Ishizuka, Takumi; Tanaka, Mio; Yamashita, Yoshihiro; Chosa, Etsuo; et al. (Histochemistry and cell biology, 2022)
High-mobility group box 2 (HMGB2) is a chromatin-associated protein that is an important regulator of gene transcription, recombination, and repair processes. The functional importance of HMGB2 has been reported in various organs, including the testis, heart, and cartilage. However, its role in the ovary is largely unknown. In this study, ovary tissues from wild-type (WT) and HMGB2-knock-out (KO) mice were examined by histopathological staining and immunohistochemistry. The ovary size and weight were significantly lower in HMGB2-KO mice than in age-matched WT littermates. Histopathological analysis revealed ovarian atrophy and progressive fibrosis in 10-month-old HMGB2-KO mouse ovaries. Compared to age-matched WT mice, the numbers of oocytes and developing follicles were significantly decreased at 2 months of age and were completely depleted at 10 months of age in HMGB2-KO mice. Immunohistochemistry revealed the expression of HMGB2 in the granulosa cells of developing follicles, oocytes, some corpora lutea, and stromal cells. Importantly, HMGB2-positive cells were co-localized with estrogen receptor beta (ERβ), but not ERα. Estrogen response element-binding activity was demonstrated by southwestern histochemistry, and it was decreased in HMGB2-KO mouse ovaries. Cell proliferation activity was also decreased in HMGB2-KO mouse ovaries in parallel with the decreased folliculogenesis. These results indicated that the depletion of HMGB2 induced ovarian atrophy that was characterized by a decreased ovarian size and weight, progressive fibrosis, as well as decreased oocytes and folliculogenesis. In conclusion, we demonstrated the crucial role of HMGB2 in mouse ovarian folliculogenesis through ERβ expression.